2009
DOI: 10.1161/circinterventions.108.825323
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Evolution of Percutaneous Coronary Intervention and Its Impact on Clinical Outcomes

Abstract: Background-Percutaneous coronary intervention (PCI) has undergone rapid progress, both in technology and adjunct therapy. However, documentation of long-term temporal trends in relation to contemporary practice is lacking. Methods and Results-We analyzed PCI use and outcomes in 8976 consecutive patients in the multicenter, National Heart, Lung, and Blood Institute- Patients undergoing PCI in the recent waves were older and more often reported comorbidities than those in the balloon era. PCI was more often perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 25 publications
1
39
0
4
Order By: Relevance
“…This is likely a result of the much larger patient sample size and the greater frequency of comorbidities including prior coronary events, stroke, and atherosclerosis risk factors compared with other studies. 33 Our results in a cohort receiving coronary stents are similar to the conclusions of the CHARISMA trial in a nonstented population with stable vascular disease, in which prolonged dual antiplatelet therapy lowered clinical events by 17% over 30 months without increasing major bleeding in subgroup of high-risk patients with prior myocardial infarction or stroke or symptomatic peripheral artery disease. 34 This difference might even be greater in patients with acute coronary syndrome, because the CURE trials showed a 20% reduction in events over 1 year.…”
Section: Relationship Of Events To Very Late Stent Thrombosis and Tarsupporting
confidence: 81%
“…This is likely a result of the much larger patient sample size and the greater frequency of comorbidities including prior coronary events, stroke, and atherosclerosis risk factors compared with other studies. 33 Our results in a cohort receiving coronary stents are similar to the conclusions of the CHARISMA trial in a nonstented population with stable vascular disease, in which prolonged dual antiplatelet therapy lowered clinical events by 17% over 30 months without increasing major bleeding in subgroup of high-risk patients with prior myocardial infarction or stroke or symptomatic peripheral artery disease. 34 This difference might even be greater in patients with acute coronary syndrome, because the CURE trials showed a 20% reduction in events over 1 year.…”
Section: Relationship Of Events To Very Late Stent Thrombosis and Tarsupporting
confidence: 81%
“…As shown in the National Heart, Lung, and Blood Institute (NHLBI) Dynamic Registry, the percentage of patients with myocardial infarction undergoing PCI rose from 23% to 36% between 1998 and 2006. 10 This was accompanied by a significant increase in urgent and emergent cases. Although the distribution of STEMI versus NSTEMI had been reported to be equivalent (ranging from 30% to 60%), 6 recent evidence suggests a shift to more PCI procedures in NSTEMI patients than in STEMI patients.…”
mentioning
confidence: 99%
“…In particular, the development of bare metal stents and, more recently, drug-coated stents, modern angioplasty balloon catheters and equipment, and safer while more effective antiplatelet therapy has improved procedural success and reduced mortality. 11 Indeed, patients with higher degrees of multivessel disease, as well as concomitant comorbidities, are increasingly offered PCI with maintained outcomes. 11 This is confirmed by the dramatic shift toward PCI for the majority of patients presenting with coronary artery disease, as opposed to bypass surgery, as well as recent trends toward increased multivessel and left main PCI.…”
mentioning
confidence: 99%
“…11 Indeed, patients with higher degrees of multivessel disease, as well as concomitant comorbidities, are increasingly offered PCI with maintained outcomes. 11 This is confirmed by the dramatic shift toward PCI for the majority of patients presenting with coronary artery disease, as opposed to bypass surgery, as well as recent trends toward increased multivessel and left main PCI. 12 However, progress in advanced PCI, as well as the management of acute myocardial infarction and advanced heart failure, including both acute decompensated failure and cardiogenic shock, has perhaps hit a plateau in the sickest patients.…”
mentioning
confidence: 99%